Photographs illustrating the earliest times of New South Wales (1880)
Photographic reproductions of early watercolours and engravings of Sydney; with later panoramas of the city.
Keywords: Sydney (N.S.W.) -- History -- to 1850.; Sydney (N.S.W.) -- Pictorial works